Electrical Stimulation Followed by Mesenchymal Stem Cells Improves Anal Sphincter Anatomy and Function in a Rat Model at a Time Remote From Injury. Issue 5 (May 2016) - Sun, Li; Yeh, Judy; Xie, Zhuojun; Kuang, Mei; Damaser, Margot S.; Zutshi, Massarat
Abstract : BACKGROUND: We have explored cell-based therapy to aid anal sphincter repair, but a conditioning injury is required to direct stem cells to the site of injury because symptoms usually manifest at a time remote from injury. OBJECTIVE: We aimed to investigate the effect of local electrical stimulation followed by mesenchymal stem cell delivery on anal sphincter regeneration at a time remote from injury. DESIGN AND MAIN OUTCOME MEASURES: With the use of a rat model, electrical stimulation parameters and cell delivery route were selected based on in vivo cytokine expression and luciferase-labeled cell imaging of the anal sphincter complex. Three weeks after a partial anal sphincter excision, rats were randomly allocated to 4 groups based on different local interventions: no treatment, daily electrical stimulation for 3 days, daily stimulation for 3 days followed by stem cell injection on the third day, and daily electrical stimulation followed by stem cell injection on the first and third days. Histology-assessed anatomy and anal manometry evaluated physiology 4 weeks after intervention. RESULTS: The electrical stimulation parameters that significantly upregulated gene expression of homing cytokines also achieved mesenchymal stem cell retention when injected directly in the anal sphincter complex in comparison with intravascular and intraperitoneal injections. Four weeks after intervention, there was significantly more new muscle in the area of injury and significantly improved anal resting pressure in the group that received daily electrical stimulation for 3 days followed by a single injection of 1 million stem cells on the third day at the site of injury. LIMITATION: This was a pilot study and therefore was not powered for functional outcome. CONCLUSIONS: In this rat injury model with optimized parameters, electrical stimulation with a single local mesenchymal stem cell injection administered 3 weeks after injury significantly improved both new muscle formation in the area of injury and anal sphincter pressures.